2012
DOI: 10.1186/1750-1326-7-3
|View full text |Cite
|
Sign up to set email alerts
|

Both common variations and rare non-synonymous substitutions and small insertion/deletions in CLU are associated with increased Alzheimer risk

Abstract: BackgroundWe have followed-up on the recent genome-wide association (GWA) of the clusterin gene (CLU) with increased risk for Alzheimer disease (AD), by performing an unbiased resequencing of all CLU coding exons and regulatory regions in an extended Flanders-Belgian cohort of Caucasian AD patients and control individuals (n = 1930). Moreover, we have replicated genetic findings by targeted resequencing in independent Caucasian cohorts of French (n = 2182) and Canadian (n = 573) origin and by performing meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 35 publications
3
75
0
Order By: Relevance
“…Furthermore, APOE and CLU have been shown to cooperate in suppressing Aβ deposition and APOE and CLU may critically modify Aβ clearance at the blood-brain barrier, suggesting a role for clusterin in the amyloidogenic pathway. CLU levels are increased in proportion to APOE-ε4 allele dose, suggesting an induction of clusterin in individuals with low APOE levels (12).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, APOE and CLU have been shown to cooperate in suppressing Aβ deposition and APOE and CLU may critically modify Aβ clearance at the blood-brain barrier, suggesting a role for clusterin in the amyloidogenic pathway. CLU levels are increased in proportion to APOE-ε4 allele dose, suggesting an induction of clusterin in individuals with low APOE levels (12).…”
Section: Introductionmentioning
confidence: 99%
“…Harold et al in their GWAS paper had reported the variant as being in strong LD with rs11136000 (r 2 0.976, D' 0.998), which showed a similar level of association with AD as rs11136000 in their data (Harold et al 2009). In other studies, the SNP has not been found to be significantly associated with AD, perhaps due to insufficient sample sizes to give the power required (Guerreiro et al 2010;Bettens et al 2012). In the imputed data, rs7982 showed a more significant association with AD than did rs11136000.…”
Section: Discussion Of Exonic Variantsmentioning
confidence: 99%
“…Several published studies have sought to characterise the source of the association signal within CLU, generally focussing on exonic regions, and consistently, no coding variants which can explain the GWAS signal have been found (Guerreiro et al 2010;Bettens et al 2012;Ferrari et al 2012). Given the assumption that the GWAS SNP is tagging a variant or variants implicated in AD risk at the CLU locus, it is logical to turn the search to non-coding variants.…”
Section: Discussion Of Non-coding Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include CLU [4], CLU, PICALM and CR1 [5], ABCA7 [6] and ABCA7, BIN1, CD2AP, CLU, CR1, EPHA1, MS4A4/MS4A6A [7]. All studies, apart from [5], have used targeted exome sequencing, ignoring variants which may be found in the noncoding and intronic regions of the loci.…”
Section: Introductionmentioning
confidence: 99%